Genomics and epigenomics in novel schizophrenia drug discovery: translating animal models to clinical research and back. (February 2015) - Bosia, Marta; Pigoni, Alessandro; Cavallaro, Roberto
<x xml:space="preserve">Abstract</x> Introduction: Schizophrenia is a major psychiatric disorder that afflicts about 1% of the world's population, falling into the top 10 medical disorders causing disability. Existing therapeutic strategies have had limited success; they have poor effects on core cognitive impairment and long-term disability. They are also burdened by relevant side effects. Although new antipsychotic medications have been launched in the past decades, there has been a general lack of significant innovation over the past 60 years. This lack of significant progress in the pharmacotherapy of schizophrenia is a reflection of the complexity and heterogeneity of its etiopathogenetic mechanisms. Areas covered: In this article, the authors briefly review genetic models of schizophrenia, focusing on examples of how new therapeutic strategies have been developed from them. They report on the evidence of epigenetic alterations in schizophrenia and their relevance to pharmacological studies. Further, they describe the implications of epigenetic mechanisms in the etiopathogenesis of the disease and the effects of current antipsychotic drugs on epigenetic processes. Finally, they provide their perspective of using epigenetic drugs for treating schizophrenia. Expert opinion: Current genetic and epigenetic studies are finally shedding light on the biomolecular mechanisms linked to the core pathogenetic alterations in schizophrenia, rather than just their symptoms. These advancements in the understanding of the physiopathology of schizophrenia provide exciting new perspectives for treatments. Indeed, the possibility of looking directly at the biomolecular level allows us to bypass the age-old issues of animal studies pertaining to their questionable validity as behavioral models.